History Of Borte Khatun: Symbol Of Loyalty, Politics And Patience (The Peerian Journal, 2025)
This article examines the life of Genghis Khan's wife, Borte Khatun, her political influence, and historical role. She is known for her involvement in Mongol traditions, marriage ceremony, kidnapping by the Merkits, and subsequent rescue. Borte was Genghis Khan's loyal advisor and most trusted wife, actively participating in imperial politics. She also played a major role in prioritizing Genghis Khan's children. Borte remains in history not only as a devoted wife but also as an important political figure in maintaining the stability of the Mongol Empire